Pemanfaatan Media Digital Pada Sistem Pemerintahan: Studi Literatur Berbantuan Nvivo 12 Pro - Maslia Qomar; Zulkifli Muhadli (Universitas Hamzanwadi, 2023)
Information technology has changed the pattern of service to the public to be faster, more precise, wider, and more transparent. The obstacle faced by governments in developing countries is the rapid dissemination of information to various regions to the most remote areas, such as villages and even hamlets. One of the efforts to disseminate information from the government is through the internet. The development of technology in public services is a practical solution in the current technological era. The acceleration of technology has long touched the government sector, in the form of electronic government or e-government e-gov. Comprehensive e-government implementation from the village government level to the center. Various studies have focused on the development and implementation of e-government, so in this study, a literature review was carried out using the PRISMA method with results mapping by the Nvivo Pro 12 program. digital media, both for the internal administration of employees and in public services. A total of 20 articles were mapped into four criteria, including